Corporate purpose: from a `Tower of Babel' phenomenon towards construct clarity - Nikolai Brosch (Journal of Business Economics, 2023)
In recent years, interest in corporate purpose has gained momentum among both practitioners and academic researchers. Despite this, the construct of corporate purpose is still under-conceptualized and suffers from multiple – and partly divergent – understandings. Given that a field's development is shaped by the clarity of its constructs, this paper strives to evolve the construct of corporate purpose from a `tower of babel' phenomenon towards construct clarity. To this end, it reviews and synthesizes the literature on corporate purpose and proposes a definition that integrates different approaches. In addition, this paper underpins the definition with seven core characteristics of corporate purpose, delineates scope conditions and elaborates on the relationship of corporate purpose with related concepts including mission, vision, corporate social responsibility and sustainability. By enhancing construct clarity, the paper paves the avenue for further research on corporate purpose and the further development of the field.
Keywords: L10; L21; M10; M14; Q01; 650; Corporate purpose; Mission; Vision; Corporate social responsibility; Construct clarity